Methodology of Education of Specialists in Industrial Enterprises using for Site Technology on the Effect of Electricity on the Human Body - O. D., Rakhimov; Б., Каримов (European Journal of Life Safety and Stability (2660-9630), 2022)
The article provides important information about the role of electricity in the development of industries, the need for electricity in Uzbekistan, alternative energy sources. Accidents under the influence of electricity are analyzed, a classification of factors determining the impact of electric current on the human body is developed. As an innovative pedagogical technology for training specialists in electrical safety in industrial enterprises, the classification of foresight technology methods and the analysis of foresight research are presented. A methodology for using foresight methods in teaching has been developed and is based on examples.